Penerapan Teknologi Destilasi Sebagai Alternatif Penyediaan Air Bersih Di Kabupaten Kendal - Herwindo, Wildan; Bumi, Ingerawi Sekaring; Puspita, Annisa Sila; Sulistianingsih, Anis; Iryanti, Yuny; Bahri, Syamsul; Patiroi, Andi; Hetwisari, Tia (LOSARI DIGITAL, 2026)
Coastal areas in northern Java are experiencing tidal flooding due to a combination of land subsidence, sea level rise, and climate change. This situation has a direct impact on the community's limited access to fresh water for domestic needs. The availability of seawater in the surrounding area can be utilized as an alternative source of clean water. An alternative that can applied to address this problem is distillation technology as an appropriate technology for processing seawater into fresh water. Distillation technology is relatively simple, does not require complex systems, and can be developed and replicated in various coastal locations. Through this community service activity, training was provided to the community on the working principlesand operation of distillation. The activity results have shown a positive response, showed by increased community understanding and skills in seawater treatment, as well as growing awareness of the importance of utilizing technologies.